Radiofrequency ablation of hepatocellular cancer: Complication and residual tumor rates (Annals of Medical Research, 2021)
None
Keywords: Hepatocellular Carcinoma; Radiofrequency Ablation Treatment; Complication rate; Technical Success Rate.br /